2019
DOI: 10.5505/ktd.2019.54871
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 levels in patients with chronic telogen effluvium.

Abstract: ÖZ GİRİŞ ve AMAÇ: Saç dökülmesinin pek çok formunda bazı vitaminlerin önemli rol oynadığı iyi bilinmektedir. Fakat vitamin B12 (vit B12) nin saç dökülmesinin ptogenezindeki rolü hala açık değildir. Bu çalışmada Kronik Tleogen Efluvium (KTE) ile vit B12 düzeyleri arasındaki ilişkiyi değerlendirmeyi amaçladık. YÖNTEM ve GEREÇLER: Dermatoloji polikliniğinde KTE tanısı alan hastalardan hasta grubu oluşturuldu. Kontrol grubu hiçbir sistemik ve dermatolojik hastalığı olmayan Vit B12 düzeyi check up polikliniğinde öl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…The number of patients with the highest abnormalities in all parameters was observed in TE and females; therefore, we particularly suggest examining patients with TE and female patients first. More studies had been reported on laboratory abnormalities in TE, and they may also support our suggestion [ 12 , 17 , 17 , 27 29 ]. After vitamin D deficiency in both sexes, investigation ferritin and hemoglobin deficiency in females and vitamin B12 deficiency in males may be recommended.…”
Section: Discussonsupporting
confidence: 90%
See 2 more Smart Citations
“…The number of patients with the highest abnormalities in all parameters was observed in TE and females; therefore, we particularly suggest examining patients with TE and female patients first. More studies had been reported on laboratory abnormalities in TE, and they may also support our suggestion [ 12 , 17 , 17 , 27 29 ]. After vitamin D deficiency in both sexes, investigation ferritin and hemoglobin deficiency in females and vitamin B12 deficiency in males may be recommended.…”
Section: Discussonsupporting
confidence: 90%
“…Vitamin B12 is suggested to have a role in hair follicle proliferation, as it is essential for DNA synthesis [ 17 18 ]. 2 However, there is still no sufficient data to recommend supplementation of vitamin B12 in TE, AGA, and AA [ 1 ].…”
Section: Discussonmentioning
confidence: 99%
See 1 more Smart Citation